2023
DOI: 10.1113/jp283792
|View full text |Cite
|
Sign up to set email alerts
|

Adapting to a new environment: postnatal maturation of the human cardiomyocyte

Abstract: support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 228 publications
(418 reference statements)
0
7
0
Order By: Relevance
“…Finally, we note that others have observed significantly slower and smaller calcium transients in pediatric cardiomyocytes 12,30 . We observed a statistically significant increase in calcium amplitude with older age ( Figure 5 ), which can also be influenced by structural changes to the cardiomyocyte (i.e., sarcoplasmic reticulum calcium content, t-tubule development) 7 that are not included within this computational model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we note that others have observed significantly slower and smaller calcium transients in pediatric cardiomyocytes 12,30 . We observed a statistically significant increase in calcium amplitude with older age ( Figure 5 ), which can also be influenced by structural changes to the cardiomyocyte (i.e., sarcoplasmic reticulum calcium content, t-tubule development) 7 that are not included within this computational model.…”
Section: Resultsmentioning
confidence: 99%
“…During postnatal life, the mammalian heart undergoes a series of developmental changes that facilitate the transition from the intrauterine to extrauterine environment. Throughout this developmental process, cardiomyocytes adjust to hemodynamic demands by increasing their size, enhancing structural organization, and adapting their electrophysiological and contractile properties 7 . Studies suggest that human cardiomyocytes evolve within the first year of life – but, may not reach full maturity until nearly a decade after birth.…”
Section: Introductionmentioning
confidence: 99%
“…This higher weighting may also be of use to improve the performance of single ECG afflicted pairs with left bundle branch abnormality, for example. The performance drops seen in the paediatric cases, indicative of rapidly changing cardiac electrophysiology 43 and thus ECG biometric features, suggest the need for future studies to focus on paediatric performance.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may be attributed to the species differences and the experimental model used in each study. As examples, rodent ventricular cardiomyocytes have a shorter action potential duration and rely more heavily on the sarcoendoplasmic reticulum calcium ATPase for calcium removal compared to human cells (Bers 2008; Ripplinger et al 2022); yet, hiPSC-CM do not fully replicate adult human ventricular myocytes given their automaticity and immature calcium handling machinery (Karbassi et al 2020; Salameh et al 2023). Nevertheless, comparative studies have demonstrated excellent correlation between FPDc measurements in hiPSC-CM and clinical QTc measurements in response to pharmacological agents – supporting the use of hiPSC-CM as a translational model and screening tool for toxicological assessments (Blinova et al 2017).…”
Section: Discussionmentioning
confidence: 99%